Appraisal in history: Construals of significance, fortune, and status. (28th May 2018) - Myskow, Gordon
Abstract : This article explores issues in applying Martin and White's (2005) Appraisal framework to historical discourse. It outlines several modifications to the existing set of Appraisal tools to account for the following key evaluative aspects of history texts: (1) significance (2) fortune and (3) status. Resources for construing Significance (Salience, Depth (of Impact), Quantity and Distribution) are located in the Appreciation region of the Attitude network. A high/low parameter is proposed to account for how significance is scaled in terms of degree. Resources for construing Fortune and Status are located in the Judgment framework as subcategories of 'Normality'. A 'cline of contentiousness' through the subcategories of Judgment is proposed to account for the gradation of contentiousness from the comparatively low-stakes evaluations of Fortune and Status to the highest-stakes judgments of Veracity and Propriety. Proposed revisions to the Appraisal framework are discussed in connection with key concepts in the literature of historiography.